Unscripted economics in an industrial community. (3rd February 2020) - Duggan, Marie Christine
One third of US manufacturing jobs disappeared between 2001 and 2009 and the conventional explanations (low wages overseas, robots taking over) do not apply to the capital goods producers in Keene, New Hampshire, where the author teaches. Local firms compete with high wage counterparts and firms using robots hire people as well. De/reindustrialisation ascertains the cause(s) of industrial contraction – or success. Students visit plants in the local industrial base and conduct oral history interviews, analyse annual reports and apply specific concepts of economic theory. The course is interdisciplinary, involves undergraduate research and civic engagement and uses open education assignments. Unscripted learning has proved the great motivator, as students navigate their oral history interviews and the community presentation. The course succeeds in motivating students and it serves the community, conveys research skills and pushes the teacher to take economic theory in practical directions.